Leptin activates distinct projections from the dorsomedial and ventromedial hypothalamic nuclei - Elmquist, Joel K. (The National Academy of Sciences, 1998)
Leptin has profound effects on feeding, metabolism, and neuroendocrine status. Evidence indicates that the hypothalamus coordinates these responses, though the specific brain pathways engaged by leptin remain obscure. The paraventricular nucleus of the hypothalamus (PVH) regulates pituitary gland function and feeding, and innervates autonomic preganglionic neurons, making it a candidate to regulate many of the responses to leptin. The subparaventricular zone, an anterior hypothalamic region receiving dense innervation from the suprachiasmatic nucleus, is thought to integrate circadian and metabolic information. We investigated the distribution of neurons in the rat brain activated by leptin administration that also project to the PVH or the subparaventricular zone by coupling immunohistochemistry for Fos with retrograde transport of cholera toxin-b. Intravenous leptin characteristically activated several cell groups including the ventromedial hypothalamic nucleus, the dorsomedial hypothalamic nucleus (DMH), and the PVH. When tracer injections were centered in the subparaventricular zone, many double-labeled cells were observed in the dorsomedial subdivision of the ventromedial hypothalamic nucleus. This projection may provide an anatomic substrate for integration of metabolic and circadian information to regulate the hypothalamo-pituitary axis. When cholera toxin-b injections were centered in the PVH, many double-labeled cells were found within the caudal DMH. Hence, activation of specific neuroendocrine and autonomic elements of the PVH may be triggered by leptin-activated afferents arising in the DMH. Our results demonstrate that a discrete set of hypothalamic pathways may underlie leptin’s autonomic, endocrine, and behavioral effects.